Theoretical Analysis of the Use of Social Scenario-Based “Diversity Card” Media in Tolerance Learning - Cindy Angga Setyawati (Journal of Education and Teaching Learning, 2026)
Learning tolerance in PPKn subjects still focuses on cognitive aspects through conceptual explanations and memorization, so that students' tolerant attitudes have not been fully realized in everyday life. The use of "Diversity Cards" based on social scenarios is one of the uses of learning media to teach students about tolerance. The purpose of this study is to analyze the use of these media theoretically. The study uses a qualitative approach, which is a type of literature study, in which relevant scientific literature is analyzed. Content analysis involves data reduction, theme categorization, and concept synthesis. The results of the study indicate that combining game–based media with a social scenario approach can help students learn tolerance with more active involvement, social experience, empathy, and social skills. Theoretical synthesis shows that the "Diversity Cards" media based on social scenarios can serve as an alternative to a more contextual, interactive, and focused tolerance learning approach to strengthening students' character.